BAZ2B haploinsufficiency as a cause of developmental delay, intellectual disability, and autism spectrum disorder. Issue 5 (7th February 2020) - Scott, Tiana M.; Guo, Hui; Eichler, Evan E.; Rosenfeld, Jill A.; Pang, Kaifang; Liu, Zhandong; Lalani, Seema; Bi, Weimin; Yang, Yaping; Bacino, Carlos A.; Streff, Haley; Lewis, Andrea M.; et al.
Abstract: The bromodomain adjacent to zinc finger 2B gene ( BAZ2B ) encodes a protein involved in chromatin remodeling. Loss of BAZ2B function has been postulated to cause neurodevelopmental disorders. To determine whether BAZ2B deficiency is likely to contribute to the pathogenesis of these disorders, we performed bioinformatics analyses that demonstrated a high level of functional convergence during fetal cortical development between BAZ2B and genes known to cause autism spectrum disorder (ASD) and neurodevelopmental disorder. We also found an excess of de novo BAZ2B loss‐of‐function variants in exome sequencing data from previously published cohorts of individuals with neurodevelopmental disorders. We subsequently identified seven additional individuals with heterozygous deletions, stop‐gain, or de novo missense variants affecting BAZ2B . All of these individuals have developmental delay (DD), intellectual disability (ID), and/or ASD. Taken together, our findings suggest that haploinsufficiency of BAZ2B causes a neurodevelopmental disorder, whose cardinal features include DD, ID, and ASD.